PENERAPAN E-BOOK ABC UNTUK MENINGKATKAN HASIL BELAJAR PADA SISWA DISLEKSIA - Insafvilla Surya Romadhan, Vivi; Kusumawati, Naniek; Intan Cahyaningtyas, Tiara (CV. Lafadz Jaya, 2024)
Dyslexia is a form of difficulty understanding letters or words in writing. Dyslexia disorders in children are influenced by several factors. This research uses the ABC E-book to help dyslexic students recognize capital and small letters and spell syllables and there are pictures to make it easier for students to learn to arrange letters. E-books or electronic books are books in digital format that contain text and images. This type of research uses development research or Research and Development (R & D). The development model used is ADDIE (Analyze Design Develop Implement and evaluate). The learning outcomes of dyslexic students increased after the pretest and posttest were carried out. The pretest was carried out before implementing the ABC E-book media and produced an average score of 67.5% from 4 dyslexic students. After using the ABC E-book, which was designed to make reading and recognizing letters easier, the posttest showed an increase in the average score to 90%. shows that the ABC E-book media is effective in improving Indonesian language learning outcomes for dyslexic students. This research aims to improve the learning outcomes of dyslexic students through the development of ABC E-book media, especially in Indonesian language material Chapter 8